Filozofia a etyka stosowana. Dyskusja nad propozycją Richarda Rorty`ego - Kamińska, Gabriela (Annales. Etyka w Życiu Gospodarczym, 2008)
In this article the relations between philosophy and applied ethics are considered. The presented deliberation is concentrated on the question whether philosophy has contributed to applied ethics, especially to business ethics. Trying to find an answer to this question I will refer to the discussion which was started by R. Rorty in which he presented his own point of view on the issues related to moral development and the role of philosophy and philosophers in the modern world. Rorty points at proper tools which, in his opinion, can be helpful to business ethicists and formulates the goal they should try to aim at. His opinions has started a vivid discussion. Patricia H. Werhane, Daryl Koehn and Richard T. De George try to discuss with Rorty’s statement. They oppose Rorty’s argument that philosophy is not more relevant to applied ethics than any other academic disciplines. They point to the facts which document philosophers’ contribution in forming business ethics. This article presents their arguments as well as an attempt of their critical assessment.